'Quality' at a cost: the politics of teacher education policy in Australia. Issue 4 (8th August 2021) - Barnes, Melissa; Cross, Russell
ABSTRACT: Amid this global landscape for education and policy, this paper focuses on the subject of teacher quality through the lens of teacher education reform and one particular Australian policy initiative: The Literacy and Numeracy Test for Initial Teacher Education (LANTITE). Introduced by the federal Australian government in 2016 as a gate-keeping mechanism for students entering teacher education, we apply a four-dimensional framework to analyse LANTITE's role as a reform measure aimed at improving teacher education, and its impact on shaping understandings of 'teacher quality' and 'quality teacher education' in relation to the broader field.